SELF-CONCEPT OF MADRASAH IBTIDAIYAH AND PRIMARY SCHOOL TEACHERS IN SAMBAS DISTRICT, WEST KALIMANTAN - Rasnam Rasyidi; Suaidi, Siti Muhibah; Ratu Amalia Hayani; Iwan Ridwan (International Journal of Teaching and Learning, 2024)
The purpose of this study is to compare the self-perceptions of elementary school instructors and those of teachers at Madrasah Ibtidaiyah. Are they similar or different? A quantitative comparison or comparison approach is employed. Questionnaires are used as data collecting tools and as survey methodologies. t test for independent sample data analysis method. The study's findings indicate that elementary school teachers have a self-confidence level of 77.58%, whereas Madrasah Ibtidaiyah instructors have a self-confidence level of 76.04%. The mean difference test findings indicate a probability value of 0.294 > 0.05 and a t value of -1.060. Therefore, it may be said that teachers who work in different